PENGARUH KUALITAS PELAYANAN DAN MUTU PRODUK TERHADAP KEPUASAN NASABAH TABUNGAN SIMANIS PADA PT. BPR RAGA DANA SEJAHTERA - Faivadril Ugra; Febsri Susanti (LP2M Universitas Bina Bangsa, 2023)
This study aims to examine and analyze the effect of service quality and product quality on customer satisfaction at Simanis Savings at PT. BPR Raga Dana Sejahtera. This type of research is quantitative research with multiple linear regression data analysis. The samples of this study were customers of PT. BPR Raga Dana Sejahtera who were still active, customers who made service transactions of PT. BPR Raga Dana Sejahtera in the last three months and customers who were more than seventeen years old. Data were collected using a questionnaire. The variables in this study are independent variables, namely physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), empathy (X5), and product quality (X6) and the dependent variable (Y) is customer satisfaction. From the t-test calculation, it can be seen that all independent variables have a large t-count value of t-table and a significant value <0.05 for N = 125, so the conclusion is that the hypothesis can be accepted or proven true for the physical evidence variable (X1), reliability (X2) , responsiveness (X3), assurance (X4), empathy (X5), and product quality (X6) have a positive and partially significant effect on customer satisfaction